Respuesta :
Answer: x = 2, y = 4/2
Step-by-step explanation:
Solve the System of Equations
x + 3y = 6 6x − 6y = 4
Subtract 3y from both sides of the equation.
x = 6 − 3y 6x − 6y = 4
Replace all occurrences of x with 6 − 3y in each e quation.
Replace all occurrences of x in 6x − 6y = 4 with 6 − 3y.
6 (6 − 3y) − 6y = 4
x = 6 − 3y
Simplify 6 (6 − 3y) − 6y.
36 − 24y = 4
x = 6 − 3y
Solve for y in the first equation.
Move all terms not containing y to the right side of the equation.
−24y = −32
x = 6 − 3y
Divide each term by −24 and simplify.
y = 4/3
x = 6 − 3y
Replace all occurrences of y with 4/3 in each equation.
Replace all occurrences of y in x = 6 − 3y with 4/3
x = 6 − 3 ( 3 )
y= 4/3
Simplify 6 − 3 ( 4 )
x = 2
y = 4/3
The solution to the system is the complete set of ordered pairs that are valid solutions.
(2, 4 /3 )
The result can be shown in multiple forms.
Point Form: 2, 4 /3
Equation Form: x = 2, y = 3